1996
DOI: 10.1017/s0007485300035033
|View full text |Cite
|
Sign up to set email alerts
|

Food web dynamics of irrigated rice fields at five elevations in Luzon, Philippines

Abstract: The above-water food webs of arthropod communities in irrigated rice fields on Luzon Island, Philippines, were studied over the growing season at five sites (Los Banos, Cabanatuan, Bayombong, Kiangan, Banaue) ranging in elevation from 22 m to 1524 m. Arthropod populations were vacuum-sampled at roughly weekly intervals from the date after seedlings were transplanted to flowering at each site. Site-and time-specific webs were constructed from a 687-taxa cumulative Philippines web and time-series of species pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 58 publications
3
31
0
Order By: Relevance
“…For example, even in the well-studied maize monoculture in north-central North America, there are more than 600 nontarget species (Warters 1969), of which nearly half have an unknown ecological role. The state of knowledge is similar for rice in Japan (Takahashi 1989) and in the Philippines (Schoenly et al 1996) and is likely to be worse for other crops and for nonagricultural ecosystems.…”
Section: Species Selection Criteriamentioning
confidence: 99%
“…For example, even in the well-studied maize monoculture in north-central North America, there are more than 600 nontarget species (Warters 1969), of which nearly half have an unknown ecological role. The state of knowledge is similar for rice in Japan (Takahashi 1989) and in the Philippines (Schoenly et al 1996) and is likely to be worse for other crops and for nonagricultural ecosystems.…”
Section: Species Selection Criteriamentioning
confidence: 99%
“…The biodiversity existent in these locations is also of interest to other scientific disciplines such as ecology and conservation biology (Schoenly et al 1996;Bambaradeniya and Edirisinghe 2008). These studies are relevant because the arthropods play an important part in the structure and operation of the ecosystems and the maintenance of the biological diversity (Price 1984;Gullan and Cranston 1995;Tscharntke et al 2007;Scherr and McNeely 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of diversity in arthropod communities in tropical areas all over the world have been published (Perfect and Cook 1994;Schoenly et al 1996;Kobayashi et al 1995;Bambaradeniya and Edirisinghe 2008;Latif et al 2009), but few on sub-tropical areas such as Southern Brazil are found in the literature at the present time.…”
Section: Introductionmentioning
confidence: 97%
“…In a crop like rice, intensive research has been carried out to study the food web patterns. Schoenly et al ( 1996 ) described 687 taxa consisting of pathogens, nematodes, mites, spiders, insects, snails and vertebrates and 10,000 consumer-resource trophic links. Rice crop is very unique in that it has three distinct ecological niches -the benthic, aquatic and the arboreal communities.…”
Section: Functional Signifi Cance Of Biodiversity In Annual Crops -A mentioning
confidence: 99%
“…Arthropods were the dominant group of invertebrates (405 species), of which 55 species were rice pest insects, and 200 species were natural enemies of pest insects. It has been established that conserving the natural enemy guild directly helps in pest suppression (Way and Heong 1994 ;Schoenly et al 1996 ;Settle et al 1996 ) . In addition to invertebrate diversity rice paddies are also home to water birds (Acosta et al 2010 ) fi shes, frogs, molluscs, rats and snakes.…”
Section: Functional Signifi Cance Of Biodiversity In Annual Crops -A mentioning
confidence: 99%